DETERMINAN PENGUNGKAPAN ISLAMIC CORPORATE SOCIAL RESPONSIBILITY (ICSR) BANK UMUM SYARIAH DI INDONESIA - Nurjannah, Laylatul Putri; Ponny ,; Delima, Zamrud Mirah (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2025)
Islamic Corporate Social Responsibility (ICSR) is a form of reporting that refers to the principles of Maqashid Syariah. The purpose of the research is to examine the factors of investment account holders, profitability, company size, and company age as determinants of ICSR in Sharia Commercial Banks registered with the Financial Services Authority (OJK) for the period 2019–2023. The purposive sampling method was used to obtain a sample of 42 companies. Data analysis used the panel data regression method with E-Views 12. The research findings indicate that ICSR is not significantly influenced by investment account holders, profitability, company size, or company age. These results indicate that there are still other internal factors that play a role as determinants of ICSR and emphasise the importance of ICSR reporting in the annual report as a basis for consideration by investors in investing in Islamic banks.